A New Classification for Ad-Hoc Network - Ragab, Ahmed Refaat Sobhy Ahmed (International Journal of Interactive Mobile Technologies (iJIM), 2020)
This paper focus on developing a new practical classification for ad-hoc networks, were all the past classifications revolve upon three main categories respectively, mobile ad- hoc network (MANET), Vehicle ad-hoc network (VANET) and Flying ad-hoc network (FANET). My new classification will illustrate Underwater vehicle ad-hoc network (UWVANET) as the fourth category in ad-hoc main classification, showing the powerful and the weakness of each category defined.